Non-mutated human tau stimulates Alzheimer’s disease-relevant neurodegeneration in a microglia-dependent manner - Ethan R. Roy; Qiang Wang; Kexin Huang; Sanming Li; Yuanyuan Fan; Estrella Escobar; Constance L. Atkins; Shuning Huang; Juan J. Herrera; Wenbo Li; Clare Pridans; Xiaobo Zhou; et al. (Scientific Reports)
Abstract The accumulation of abnormal, non-mutated tau protein is a key pathological hallmark of Alzheimer’s disease (AD). Despite its strong association with disease progression, the mechanisms by which tau drives neurodegeneration in the brain remain poorly understood. Here, we selectively expressed non-mutated or mutated human microtubule-associated protein tau (hMAPT) in neurons across the mouse brain and observed neurodegeneration in the hippocampus, especially associated with non-mutated human tau. Single-nuclei RNA sequencing confirmed a selective loss of hippocampal excitatory neurons by the wild-type tau and revealed the upregulation of neurodegeneration-related pathways in the affected populations. The accumulation of phosphorylated tau was accompanied by cellular stress in neurons and reactive gliosis in multiple brain regions. Notably, the lifelong absence of microglia significantly and differentially influenced the extent of neurodegeneration in the hippocampus and thalamus. Therefore, our study established an AD-relevant tauopathy mouse model, elucidated both neuron-intrinsic and neuron-extrinsic responses, and highlighted critical and complex roles of microglia in modulating tau-driven neurodegeneration.